“Be Careful and Don’t Forget to Pray”: Indonesian Female Journalists’ Protocol in Dealing with Harassments - Aderia, Aderia (JURNAL KOMUNIKASI INDONESIA, 2020)
Female journalists’ safety is a long ignored and forgotten thing in Indonesian journalism. It has been ignored even by the female journalists themselves. They took the safety issues as a job risk and as the things they have to face regularly. Many female journalists, even the experienced ones, tend to take harassments or violence for granted. In addition, most of Indonesian female journalists even blamed themselves for being a victim. This paper is a research study which aims to figure out how Indonesian female journalists perceived the safety issues, challenges they have to face in the field, and challenges for the implementation of safety protocol in Indonesian media houses. Using the Standpoint Theory and adapting the qualitative research, the researcher conducted in-depth interviews of 7 female journalists in Jakarta. Thisresearch shows that most of female journalists experienced harassment in the field and did nothing about it, let alone to report it to their supervisors. This research was conducted in the hope of improving the safety concerns of female journalists and aims to guide both media houses and female journalists. This study suggests that there should be an appropriate systemto maintain the female journalists’ safety. Keselamatan jurnalis perempuan Indonesia terabaikan dan terlupakan sejak lama. Bahkan, oleh jurnalis perempuan sendiri. Mereka menganggap masalah keselamatan sebagai risiko pekerjaan dan merupakan hal yang wajar. Banyak jurnalis perempuan termasuk yang berpengalaman, menerima pelecehan atau kekerasan sebagai hal biasa. Kebanyakan jurnalis perempuanbahkan menyalahkan diri sendiri ketika menjadi korban. Penelitian ini bertujuan untuk mengetahui bagaimana jurnalis perempuan Indonesia memahami isu keselamatan di lapangan, tantangan yang mereka hadapi serta hambatan untuk menerapkan protokol keselamatan di perusahaan media. Menggunakan Teori Standpoint dan metode penelitian kualitatif, peneliti melakukan wawancara mendalam dengan 7 jurnalis perempuan di Jakarta. Riset ini menemukan bahwa sebagian besar jurnalis perempuan mengalami pelecehan dan tidakmelakukan apa-apa, bahkan untuk sekadar melaporkannya kepada atasan. Studi ini dilakukan dengan harapan dapat meningkatkan perhatian terhadap keselamatan jurnalis perempuanbaik oleh perusahaan media maupun oleh jurnalis perempuan sendiri.